EXPLORING TEACHERS' EXPERIENCES WITH PROJECT-BASED LEARNING IN ONLINE ELT: CHALLENGES, STRATEGIES, AND OPPORTUNITIES - Rohmah, Farida Noor (Premise: Journal of English Education and Applied Linguistics, 2025)
Project-Based Learning (PjBL) is recognised for fostering active learning; yet, its application in entirely online English Language Teaching (ELT) is still inadequately examined, especially from the viewpoint of educators in Indonesian higher education. This study fills the gap by analysing the experiences of four English instructors at a private university in Yogyakarta. Employing a qualitative descriptive methodology, data were gathered via semi-structured interviews and thematically analysed to investigate the obstacles, tactics, and possibilities associated with implementing PjBL in online environments. The findings underscore several impediments, including insufficient student participation, issues in tracking project advancement, and difficulties in evaluating both technical and interpersonal abilities. Educators implemented solutions such as consistent consultation-driven feedback, integration of digital tools, and modified assessment techniques to tackle these challenges. The study indicates that online PjBL can improve students' digital literacy, creativity, and soft skills; however, it acknowledges structural limitations, including unequal access to technology, which may impede its wider use. These findings offer pragmatic insights for enhancing online English Language Teaching practices and contribute to the expanding literature on the adaptation of PjBL for virtual learning settings, with implications for educators, curriculum developers, and policymakers seeking more inclusive and effective digital pedagogies.